An enterprise structure approach improves index-based crop portfolio decision-making - Mzyece, Agness; Amanor-Boadu, Vincent; Ng'ombe, John N. (Frontiers in Environmental Economics, 2023)
Introduction While crop diversification indices are relatively simple and useful for quantifying the extent of crop diversification, they may not account for the potential differences in the types of crops grown. This study shows the need to complement crop diversification indices with an enterprise structure approach to improve index-based crop portfolio decision making. Methods The study uses linear regression models and nationally representative farm survey data from 7,934 farmers in Zambia. The study compares the enterprise approach and the Simpson index of diversification which is commonly used in crop diversification studies. Results and discussion We find that complementing the enterprise structure approach with the Simpson index of diversification can increase profitability by as high as 77.89% for farmers. The cassava enterprise structure had the most returns for farmers. It had a gross margin of ZMW 3,887 per hectare and was trailed by the maize/groundnuts/cotton/rice enterprise structure with a gross margin of ZMW3,681 per hectare. These results suggest that the use of aggregation crop diversification indices, without an additional enterprise structure analysis, may obscure the necessary insights needed to practically help farmers.